Engaging practices and communities in the development of interventions to promote HPV vaccine uptake: a protocol for implementing Boot Camp Translation in the private practice setting. Issue 12 (12th December 2020) - Brewer, Sarah E; Simpson, Matthew J; Rice, John D; Skendaore, Amanda; O'Leary, Sean T
Abstract : Introduction: The Healthy People 2020 report states a goal of 80% uptake of recommended vaccines among adolescents, including the human papillomavirus (HPV) vaccine. However, the rate of uptake of the HPV vaccine is estimated at 51% in 2018, which leaves young people vulnerable to morbidity and mortality from preventable, HPV-related cancers. Reasons for this are multifactorial and include factors at the level of the provider, primary care practice, patient and family, and community. The development of interventions that are responsive to these multifactorial barriers in real-world settings is a priority. Boot Camp Translation (BCT) is a community-engaged approach to message development for translating evidence-based practices into clinics and communities. This project aims to (1) Engage practices and communities in the development of interventions to promote HPV vaccine uptake and (2) Evaluate the impact of the BCT-designed intervention on practice-level HPV vaccine initiation rates. We hypothesise that the BCT-designed intervention will increase the rate of HPV vaccine initiation in the practices. Methods and analysis: This study will implement HPV-focused BCT in three counties in Colorado with a below average county-level vaccination rate. Each BCT group will design a multipronged intervention targeted at patients, parents, providers and the general community to then be disseminated in the participating practices and communities over the subsequent 6-month period. The long-term goal is to develop a replicable approach and low-cost method of increasing HPV vaccine uptake that is easily adaptable to different settings and sociodemographic contexts. Ethics and dissemination: This study is approved by the Colorado Multiple Institutional Review Board. Results will be disseminated through peer-reviewed manuscripts and conference presentations, as well as within Colorado practice-based research networks. Trial registration number: NCT04279964